Identification of Secondary Metabolite Compounds from Porphyra sp Extract and Their Potential as Antidiabetic Agents - Ukratalo, Abdul M; Buranga, Edw; Ichsan, Muh. Nurhidayat; Kaihena, Martha; Eddy, La (Futurity Medicine, 2025)
Aims: Porphyra is a type of local seaweed, referred to as runut by the community in Wassu Village, Central Maluku Regency, or sayur laut in Hukurila Village, Ambon City, Maluku Province, which the locals frequently consume. Porphyra sp. contains isoflavones, such as genistein, which has been shown to possess antidiabetic activity by inhibiting the activity of the DPP-4 enzyme. Study design: This research is pure laboratory experimental research using a completely randomised design with 5 treatments and 3 replicates. Place and Duration of Study: This research was conducted for three months at the Zoology Laboratory of the Department of Biology at FST Pattimura University. Methodology: All treatment groups underwent the anti-diabetes test for 14 days. Blood sugar level data were analysed using the Two-Way Analysis of Variance (ANOVA) test at a 95% confidence level. Results: The results showed that the Porphyra sp. extract positively contains flavonoids, triterpenoids, saponins, tannins, and alkaloids. The extract of Porphyra sp.also demonstrated the ability to lower blood glucose levels in mice induced with streptozotocin. Extract indicates that Porphyra sp. has potential as an effective antidiabetic agent due to the presence of bioactive compounds that may improve glucose metabolism and increase insulin sensitivity. Conclusion: These findings indicate that Porphyra sp., as a marine natural product, holds significant potential in the development of diabetes therapy.